Competition specific diagnostics and results for elite water polo players - Zinner, C.; Focke, T.; Sperlich, B.; Krueger, M.; Mester, J. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: In elite water polo there are certain special abilities, which are very important to achieve success during a match. Increasing importance is given to some game-related parameters such as the maximal throwing velocity, the maximal vertical jump height and the cyclical and noncyclical movements of the legs. For screening these abilities a water polo specific test battery was carried out with German elite and junior national squad members. METHODS: 15 male water polo players of the German elite and junior national squad (MW: 16.4 ± 3.0 yrs; 184.5 ± 9.2 cm; 84.0 ± 12.5 kg) participated in the study. The athletes performed four water polo specific test procedures. For measuring the cyclical movements of the legs (CM) the athletes had to carry 1/8 of their body weight above the water surface as long as possible, performing only the "Eggbeater Kick". For testing the noncyclical movements of the legs (nCM) two balls were installed in the upper two corners of a water polo goal and the athletes had to touch both balls alternately as often as possible within 60 seconds (s). Maximal throwing velocity (TV) was measured during a power shot with 5m distance to the goal with a sports radar gun. For determining the maximal vertical jump ( J) ability a modified jump-and-reach test was conducted. The athletes started in a horizontal position on the water surface and tried to reach the highest possible point on a scale. RESULTS: The results of the testing procedures were: CM 23.80 ± 7.13 s; nCM 75.87 ± 11.26 jumps/60 s; TV 68.53 ± 4.82 km/h; J 155.87 ± 8.61 cm. Positive correlations between the results of the tests were only found between the jump height and the cyclical and the noncyclical movements of the legs ( J:CM r = 0.65, p < 0.01; J:nCM r = 0.86, p < 0.01). DISCUSSION: It could be shown that there exists no correlation between maximal throwing velocity and maximal jump height. Our results are in accordance with the literature (Feltner 1994) indicating that a high ball velocity not only depends on a high vertical reach. The throwing velocity during a water polo match is affected by many more factors. However, the individual results are compared to the collected mean values and specific training recommendations are given to the coaches too increase these abilities to achieve greater success.